2018
DOI: 10.1111/cns.12986
|View full text |Cite
|
Sign up to set email alerts
|

A within‐subject consideration of the psychotic spectrum disorder concept in a patient in remission associated with cortical gray matter recovery

Abstract: The 3 discrete periods of psychopathology support the diagnosis of PSD. The unusual course and outcome, including remarkable improvement, in executive function and enhanced cortical gray matter in selective brain regions may have been the result of unique endogenous genetic and epigenetic factors and effect of medication.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

0
3
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
3
1
1

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 62 publications
0
3
0
Order By: Relevance
“…They report that at 6‐year follow‐up, these 4 psychotic diagnoses are characterized by quantitative rather than qualitative differences in psychopathology, functionality, quality of life and service engagement and suggest that these 4 diagnoses are arbitrary categories within what is, in reality, a milieu of psychosis. In a complementary manner, Meltzer and colleagues start from an alternative perspective by describing a case that, over her lifetime, has evidenced discrete, nonoverlapping periods of treatment‐resistant bipolar disorder, major depressive disorder with psychotic features and schizophrenia, followed by sustained remission. They compare initial pharmacological nonresponse, subsequent remission, and associated longitudinal neuroimaging findings in this case with those of her multiple counterparts, all of whom participated in the same clinical trial of treatment‐resistant schizophrenia.…”
mentioning
confidence: 99%
“…They report that at 6‐year follow‐up, these 4 psychotic diagnoses are characterized by quantitative rather than qualitative differences in psychopathology, functionality, quality of life and service engagement and suggest that these 4 diagnoses are arbitrary categories within what is, in reality, a milieu of psychosis. In a complementary manner, Meltzer and colleagues start from an alternative perspective by describing a case that, over her lifetime, has evidenced discrete, nonoverlapping periods of treatment‐resistant bipolar disorder, major depressive disorder with psychotic features and schizophrenia, followed by sustained remission. They compare initial pharmacological nonresponse, subsequent remission, and associated longitudinal neuroimaging findings in this case with those of her multiple counterparts, all of whom participated in the same clinical trial of treatment‐resistant schizophrenia.…”
mentioning
confidence: 99%
“…More recently, Wunderink and colleagues provocatively found that patients fared better earlier on in their illness when they stopped medication rather than being maintained on antipsychotic medications [12] . Meltzer also reports an intriguing case report of a patient whose illness was refractory over decades to multiple pharmacotherapies, yet late in life her illness appeared to remit with low doses of risperidone, and with noteworthy changes (gray matter increases) in brain structure on MRIs (Magnetic Resonance Imaging) [13] .…”
mentioning
confidence: 99%
“…At the other end of psychosis and over the course of illness, clozapine appears to be more effective than other drugs. And Meltzer's case report suggests that something changed biologically over time as exemplified by the later impact of a selective antipsychotic therapy [13] . Thus, understanding the biological trajectory and mutability of psychosis over time would be a powerful advance for our field.…”
mentioning
confidence: 99%